Roads to Change: Livelihoods, Land Disputes, and Anticipation of Future Developments in Rural Kenya - Clemens Greiner; David Greven; Britta Klagge (The European Journal of Development Research, 2021)
This article examines how rural roads relate to differences in livelihood patterns, attitudes toward social change, and land disputes in Baringo, Kenya. Although their direct use is limited for many residents, roads have a highly differentiating impact. While some households orientate themselves toward roads, those relying more on (agro-)pastoralist livelihoods avoid their proximity. Our findings suggest that better-off households are not the only ones that tend to live closer to roads, but that poorer households do as well. Rather than by socio-economic status, households living closer to roads can be characterized by higher degrees of formal education and also appear to be more open to economic and social change. Our data also highlight dynamics of land disputes in the face of ongoing large-scale infrastructural investments in Kenya's previously marginal northern drylands.
Keywords: 330; Roads; Infrastructure; Geothermal energy; Pastoralism; Quantitative analysis; East Pokot; Baringo; Kenya